2021
DOI: 10.1111/coa.13875
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of CFTR mutations in patients with chronic rhinosinusitis: A systematic review and meta‐analysis

Abstract: Patients with recalcitrant forms of chronic rhinosinusitis (CRS) that do not respond to appropriate medical and surgical management, including but not limited to nasal topical steroids, nasal irrigations and endoscopic sinus surgery, present a diagnostic and therapeutic challenge to care providers. 1 These patients tend to suffer from persisting symptoms despite traditional approaches to therapy and often require expanded treatment options and multidisciplinary approaches to care. 1 In particular, patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…TBXA2R is known to stimulate vascular endothelial cell pro-inflammatory responses [51]. CFTR, as a chloride channel, controls ion and water secretion and absorption in epithelial tissues, thereby affecting mucus production [52].…”
Section: Discussionmentioning
confidence: 99%
“…TBXA2R is known to stimulate vascular endothelial cell pro-inflammatory responses [51]. CFTR, as a chloride channel, controls ion and water secretion and absorption in epithelial tissues, thereby affecting mucus production [52].…”
Section: Discussionmentioning
confidence: 99%
“…Pinto et al found that the region of chromosome 7q31.1–7q32.1 that is associated with the CFTR gene may have a role in the development of CRS [ 72 ]. Young et al, based on reports from the USA and Europe, indicated that the prevalence of CFTR mutations in patients with CRS was 5.65% and that the prevalence of the Phe508 mutation was 4.22% [ 73 ]. According to recently reported data, CFTR polymorphism (e.g., M470V) [ 70 ] and G551D- CFTR mutation can predispose persons to CRS [ 74 ], especially CRSwNP.…”
Section: From Classical Microbiology To Molecular and Omics Methodsmentioning
confidence: 99%